1979
DOI: 10.1177/105960117900400210
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Task-Oriented Communication and Visual Impairment on Competitive Groups

Abstract: This study investigated the effects of: (1) task-oriented communication and non-task-oriented communication on group outcome and (2) visual impairment on intragroup and intergroup communication in competitive situations. Forty-eight male and female subjects participated in the Prisoner's Dilemma game. The results showed that the amount of taskoriented interaction was significant in determining goal accomplishment, while the non-task-oriented interaction was not significant in determining the outcome. Also, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…This affirms the study of Diberardinis et al (2018) as the results showed that the amount of task-oriented interaction was significant in determining goal accomplishment. Thus, Taiwo (2018) found that task-oriented communication is an exchange focusing on effectively neutral instrumental activities that are related to task accomplishment.…”
Section: 5supporting
confidence: 87%
“…This affirms the study of Diberardinis et al (2018) as the results showed that the amount of task-oriented interaction was significant in determining goal accomplishment. Thus, Taiwo (2018) found that task-oriented communication is an exchange focusing on effectively neutral instrumental activities that are related to task accomplishment.…”
Section: 5supporting
confidence: 87%
“…Thus, this type of communication is "person-oriented" [17] and "relationship-oriented" [18]. Froehl [16] coined this type of communication relationship-building communication.…”
Section: Introductionmentioning
confidence: 99%